Long-term outcomes with balloon-expandable and self-expandable prostheses in patients undergoing transfemoral transcatheter aortic valve implantation for severe aortic stenosis. (1st September 2019) - Vollenbroich, René; Wenaweser, Peter; Macht, Annina; Stortecky, Stefan; Praz, Fabien; Rothenbühler, Martina; Roost, Eva; Hunziker, Lukas; Räber, Lorenz; Windecker, Stephan; Pilgrim, Thomas
Abstract: Background: Data on long-term outcomes in patients undergoing transcatheter aortic valve implantation (TAVI) is scarce. Methods: We investigated long term outcomes of consecutive patients undergoing TAVI with balloon- and self-expandable bioprostheses (Edwards SAPIEN (ESV), Edwards Lifesciences Inc., Irvine, CA, USA; Medtronic Corevalve system (MCS), Medtronic Inc., Minneapolis, MN, USA). Results: Among 628 patients (mean age 82.4 ± 5.8 years, 55% female), 489 (77.8%) underwent transfemoral TAVI. 309 (63.2%) patients received a MCS prosthesis, whereas 180 (36.8%) patients were treated with an ESV prosthesis. The median duration of follow-up amounted to 5.2 years (range 3.4–8.3 years). All-cause mortality did not differ between the two groups (MCS 46.9%, ESV 53.4%, CI 95%: RR 1.21 [0.93–1.57], P  = 0.15), whereas cardiac mortality was higher in the ESV cohort after 5 years of follow-up (MCS 35.1%, ESV 45.4%, CI 95%: RR 1.37 [1.01–1.86], P  = 0.04). Structural valve deterioration, which was on average diagnosed 41.9 months (range 18–60 months) after TAVI, occurred in 8 cases (1.6%), resulting in one repeat intervention. Conclusions: While half of all patients died within 5 years after TAVI with no significant differences in all-cause mortality, structural valve deterioration was documented in <2% of cases. Highlights: The occurrence of structural valve deterioration (SVD) is rare (<2%). SVD is diagnosed on average 3.5 years after the index procedure. Comparing valve-types, no differences in all-cause mortality or stroke can be seen. Repeat interventions for prosthetic heart valve related problems occur sporadically.